An assessment of the effectiveness of community health clubs as drivers of standard health and hygiene in mzilikazi district, Bulawayo - Ncube, Khanyisile (Midlands State University, 2014)
This research’s main objective was to assess the effectiveness of Community Health Clubs as drivers of standard health and hygiene in Mzilikazi District, Bulawayo. Poor service delivery by Bulawayo City Council in terms of Water Sanitation and Hygiene (WASH) results in increased prevalence of diarrheal diseases which claim a lot of lives especially for children under the age of five. The research targeted Mzilikazi, Makokoba and Njube the oldest suburbs in Bulawayo where the concept of Participatory Health and Hygiene Education through CHCs was implemented to improve hygiene practices and increase community’s resiliency to Water Sanitation and Hygiene related shocks such as diarrheal disease outbreaks. Responses from the participants illustrate that Community Health Clubs empowers people to take control of their own health, promote positive hygiene behaviour and create demand for sanitation. The researcher recommends that assessments on urban hazards and risks should be continued. In making progress towards the attainment of the Millennium Development Goals the concept of Participatory Health and Hygiene Education is important. There is need for engagement between the health clubs and the City Councils because these clubs are the custodians of household health and hygiene practices and norms and are key transmitters of hygiene messages in the community hence having a major impact in reducing disease prevalence. Local authorities need to support the clubs to move from reactive crises management to proactive crises management.